Effect of Emotion on Primary School Pupils Spelling Summary - Largy, Pierre; Simoës-Perlant, Aurélie; Soulier, Lucille (Swiss Journal of Educational Research, 2018)
The aim of this study is to examine the effects of an emotional content of pictures on spelling performances, with 2nd, 3rd, 4th and 5th graders. According to the attentional resource allocation model (Ellis & Moore, 1999), emotions should monopolize a part of the attentional resource at the expense of the writing task. Creating a cognitive overload, emotional content should have a negative effect on attentional resources necessary for the writing process, affecting text size, and spelling performances. Results show an emotional content effect on spelling performances of primary school pupils.